2012
DOI: 10.1016/j.fertnstert.2012.02.026
|View full text |Cite
|
Sign up to set email alerts
|

How members of the Society for Reproductive Endocrinology and Infertility and Society of Reproductive Surgeons evaluate, define, and manage hydrosalpinges

Abstract: Objective To describe the management of hydrosalpinges among Society for Reproduction Endocrinology and Infertility (SREI)/Society of Reproductive Surgeons (SRS) members. Design Cross-sectional survey of SREI/SRS members. Setting Academic and private practice–based reproductive medicine physicians. Participant(s) A total of 442 SREI and/or SRS members. Intervention(s) Internet-based survey. Main Outcome Measure(s) To understand how respondents evaluate, define, and manage hydrosalpinges. Result(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Briefly, surveys were sent to 1078 SREI and SRS members between 25 October and 8 November 2011. Detailed methods and demographic information about the survey mailing and respondents, respectively, is described elsewhere (Omurtag et al , 2012). Respondents practising in AIM and CIM states both reported performing more IVF cycles per year than respondents practising in NoIM states.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, surveys were sent to 1078 SREI and SRS members between 25 October and 8 November 2011. Detailed methods and demographic information about the survey mailing and respondents, respectively, is described elsewhere (Omurtag et al , 2012). Respondents practising in AIM and CIM states both reported performing more IVF cycles per year than respondents practising in NoIM states.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is widely accepted that clinically significant hydrosalpinges negatively affect IVF success rates, Omurtag et al (2012) previously demonstrated that physicians differ in their reported management practices. The current work provides three pieces of evidence suggesting that insurance coverage may be responsible for some of the variation in management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of Essure microinserts for therapeutic purposes (e.g., presence of hydrosalpinx or sactosalpinx) is largely supported by international literature and advocated by scientific societies as a safe, effective, and minimally invasive alternative to salpingectomy, whereas laparoscopic treatment is contraindicated [17][18][19][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%